ENGAGING TOURIST IN THE DIGITAL ERA: THE ROLE OF TRUST TRANSFER IN LIVE STREAMING STICKINESS - Silaban, Pantas Hasiholan; Sipayung, Leonardo Davidsi; Simajuntak, Sri Ida Royani; Siagian, Yehezkiel Dosdoy (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2025)
As a reflection of tourist behavior in online spaces such as live streaming on social media, there has been an increase in engagement with stickiness behavior. Stickiness describes the level of user attention in participating in live streaming services through the creation of trust transfer. Based on a social system approach and trust transfer, this study develops a research model to understand how live streaming services influence user stickiness. This study collected data from 263 valid respondents and analyzed it using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that social factors, namely interaction and identification, each have a significant influence on trust in the streamer. Additionally, trust transfer was found to enhance user stickiness in the form of visit duration and retention in live streaming on social media. However, trust in the streamer does not have a significant relationship with increasing user retention. These findings expand the theoretical framework by integrating a social system approach with trust transfer and its impact on tourist stickiness behavior in live streaming platforms. This study contributes to the advancement of tourism development by providing insights into live streaming platforms, emphasizing the importance of features that can enhance engaging experiences for both viewers and potential tourists. This study has several limitations that can serve as guidelines for future research, particularly in further exploring the crucial role of the socio-technical approach in investigating user behavior, specifically tourist stickiness.